Genetic Instability in Cyanobacteria – An Elephant in the Room? - Jones, Patrik R. (Frontiers in Bioengineering and Biotechnology, 2014)
Many research groups are interested in engineering the metabolism of cyanobacteria with the objective to convert solar energy, CO2 and water (perhaps also N2) into commercially valuable products. Towards this objective, many challenges stand in the way before sustainable production can be realized. One of these challenges, potentially, is genetic instability. Although only a handful of reports of this phenomenon are available in the scientific literature, it does appear to be a real issue that so far has not been studied much in cyanobacteria. With this brief perspective, I wish to raise the awareness of this potential issue and hope to inspire future studies on the topic as I believe it will make an important contribution to enabling sustainable large-scale biotechnology in the future using liquid photobiological microorganisms.